ANALISIS HASIL PERTANIAN DI KOTA DENPASAR DENGAN MENGGUNAKAN SISTEM INFORMASI GEOGRAFIS - Ni Nyoman Supuwiningsih (Telematika, 2016)
Agriculture is an activity in utilizing natural resources made by humans so that they can produce food, raw materials for industrial enterprises, energy and natural balance. Imagine if a country's territory there is no agricultural land as a strategic sector or agricultural land into residential land entirely different functions then the country can not meet the primary needs due to hold human life in need of food. Food is a primary need of agricultural products should need to be increased the number of its production due to offset population. The limited agricultural land in Denpasar from year to year will affect agricultural output. Based on these problems will require analysis of agricultural products in order to determine the increase or decrease in agricultural output in Denpasar using geographic information systems and GIS ArcView 3.3 as tools that can be used as an ingredient in decision making by the government. The method used in this research is the collection of spatial data and non-spatial data, data analysis of agricultural products in their respective districts in the city of Denpasar, database creation and conduct digitized into a digital map. Results from this study is a digital map that provides information on the increase or decrease of agricultural output in 2011-2014 in each district in the city of Denpasar.